Hybrid positron-source scheme intended for the SPARC accelerator facility at the LNF - Dabagov S. B. Sultan Barasbievich; Abdrachitov S. V. Sergey Vladimirovich; Bogdanov O. V. Oleg Viktorovich; Pivovarov Yu. L. Yury Leonidovich; Tukhfatullin T. A. Timur Ahatovich (2016, 2016)
Title screen